Complex Motions and Chaos in Nonlinear Systems - Afraimovich, Valentin; Machado, José António Tenreiro; Zhang, Jiazhong (Nonlinear Systems and Complexity,, 2016)
This book brings together 10 chapters on a new stream of research examining complex phenomena in nonlinear systems-including engineering, physics, and social science. Complex Motions and Chaos in Nonlinear Systems provides readers a particular vantage of the nature and nonlinear phenomena in nonlinear dynamics that can develop the corresponding mathematical theory and apply nonlinear design to practical engineering as well as the study of other complex phenomena including those investigated within social science.